Settlement of problematic murabahah financing for civil servants at bank aceh syariah Sabang branch - Salsabila, Chindy; Susiana, Susiana (Geuthèë Institute, Aceh, 2025)
Article 23 of Law No. 21 of 2008 concerning Islamic Banking stipulates that, prior to the provision of financing, the bank must be assured of the prospective customer's ability to fulfill their obligations, one of which may be through salary deductions from Civil Servants (ASN). Bank Aceh Syariah provides financing to ASN under a murabahah contract, which requires the customer to make installment payments in accordance with the agreed terms. However, at Bank Aceh Syariah Sabang Branch, several cases of problematic financing were identified due to customers' failure to fulfill obligations under the contract. This research aims to examine the implementation of murabahah financing, identify the causes of financing default, and analyze the settlement efforts. The research method used is empirical juridical, combining interviews and literature review. The findings show that seven ASN customers were in default due to honorable discharge, dishonorable discharge, or death. Settlements included Sharia insurance claims for deceased or honorably discharged ASN, and formal warnings (somasi) as well as engagement with the customers family in cases of dishonorable discharge. It is recommended that BAS KC Sabang request additional collateral in the form of material guarantees, conduct thorough creditworthiness analysis, and apply the precautionary principle. Customers family are also expected to cooperate in resolving default cases.